Try before you buy: Determining the mediating effects of an AR virtual try-on experience on the relationship between perceived personalization and co-creation intention moderated by perceived quality - The case of Sunnies Specs - Hilario, Karl Andrei A. (Animo Repository, 2022)
As e-commerce gains traction, companies adapt through launching their own e-commerce platforms. However, compared to physical stores, there is less interactivity and engagements in e-commerce. Augmented Reality (AR) bridges this gap by providing users with a more personalized experience. With enhanced online shopping experiences made possible by personalization, the unique needs are considered by the company which encourages users to participate in value co-creation activities which increases customer loyalty and increased brand value. Value creation cannot be done by the company alone; the involvement of customers is equally important. Thus, this study examines the mediating effect of an AR digital experience on the relationship between perceived personalization and value co-creation intention and the moderating effect of perceived service quality on the said relationship. Structural Equation Modeling (SEM) was employed using data gathered from 400 survey respondents. Findings show that personalized services encourage users to co-create value by sharing their experiences or joining corporate activities. The relationship between perceived personalization and value co-creation is partially explained by trust which highlights the importance of building trust towards the use of AR. Lastly, perceived service quality strengthens the relationship between perceived personalization and value co-creation intention as mediated by perceived trust. Therefore, employing personalization strategies is recommended for users to participate in value co-creation activities. Future research may explore other factors that influence value co-creation intention in the Philippines.